2017
DOI: 10.1111/jcpt.12655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ribonucleotide reductase M1 expression on overall survival in patients with pancreatic cancer receiving gemcitabine chemotherapy: A literature‐based meta‐analysis

Abstract: Summary What is known and objective The prognostic value of ribonucleotide reductase M1 (RRM1) in patients with pancreatic cancer receiving gemcitabine chemotherapy has been evaluated in several studies. However, the conclusions remain controversial. Methods By searching the PubMed and Embase databases, we conducted a meta‐analysis to evaluate the prognostic significance of RRM1 expression in patients with pancreatic cancer receiving gemcitabine chemotherapy. Studies were pooled, and the hazard ratio (HR) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Inhibition of RR induced by dFdCDP is the most significant mechanism for the enhancement of gemcitabine activity [20,21]. A recent meta-analysis revealed that patients with high RRM1 expression had largely poorer OS and DFS than those with low RRM1 expression [46,47], suggesting that the expression of RRM1 is an indicator of poor survival in patients with pancreatic cancer accepting gemcitabine chemotherapy [46]. Experiments confirmed that overexpression of RRM1 and RRM2 proteins of the pancreatic cancer cell line can achieve stable genetic gemcitabine resistance [48,49].…”
Section: Gemcitabine Resistance Mechanismsmentioning
confidence: 99%
“…Inhibition of RR induced by dFdCDP is the most significant mechanism for the enhancement of gemcitabine activity [20,21]. A recent meta-analysis revealed that patients with high RRM1 expression had largely poorer OS and DFS than those with low RRM1 expression [46,47], suggesting that the expression of RRM1 is an indicator of poor survival in patients with pancreatic cancer accepting gemcitabine chemotherapy [46]. Experiments confirmed that overexpression of RRM1 and RRM2 proteins of the pancreatic cancer cell line can achieve stable genetic gemcitabine resistance [48,49].…”
Section: Gemcitabine Resistance Mechanismsmentioning
confidence: 99%
“…Ribonucleotide reductase large subunit M1 (RRM1) is a rate-limiting enzyme of the DNA synthesis pathway, and is depended on for the conversion of ribonucleotides to dNTPs [ 14 ]. Studies have shown that increased levels of RRM1 are associated with resistance to gemcitabine [ 15 , 16 ]. RRM1 has also been reported to affect disease prognosis of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Putative biochemical mechanisms of gemcitabine resistance include the decreased expression of human equilibrative nucleoside transporter‐1 (hENT1) that is indispensable for cellular uptake of gemcitabine, 36 the inactivation of deoxycytidine kinase (dCK) that is a late‐limiting enzyme for metabolic activation of gemcitabine, 37 and the overexpression of RRM1 that sustains DNA synthesis, thus counteracting the pharmacological action of gemcitabine 29 . These molecular alterations found in the tumors were associated with poor survival of pancreatic cancer patients undergoing treatment with gemcitabine in various clinical settings 38,39 . Recent experimental approaches aimed at overcoming the acquired resistance to gemcitabine include targeting of hENT1 expression by TS inhibitor and bypassing nucleoside transporters by prodrugs.…”
Section: Discussionmentioning
confidence: 99%
“…29 These molecular alterations found in the tumors were associated with poor survival of pancreatic cancer patients undergoing treatment with gemcitabine in various clinical settings. 38,39 Recent experimental approaches aimed at overcoming the acquired resistance to gemcitabine include targeting of hENT1 expression by TS inhibitor and bypassing nucleoside transporters by prodrugs. Other approaches F I G U R E 4 Changes in expression of RRM1, GSK3β and cell cycle regulatory molecules in BxPC-3 cells and gemcitabine-resistant clones following GSK3β inhibition.…”
Section: Discussionmentioning
confidence: 99%